Nas tramas da pesquisa-formação: uma abordagem experiencial de autoria feminina no processo de formação docente - Leão, Maria da Graça (Universidade do Vale do Rio dos Sinos, 2009)
The theme of this thesis is located at the borders between education, feminism and literature. The goal of this research consists in analyzing the experience of feminine authorship in the process of teacher’s formation, finding support in the research-formation methodology according to Marie Christine Josso. The autobiographical reports appear as potentializers of reflections, constitutive elements of this experiential approach related to the professional formation, in which the process of autopoiésis produces regenerating interactions of the personal and professional projects, establishing the connection of gender determinations with the teaching exercise. It seeks to understand the netting of social exclusion in relation to women’s invisibility in the cultural field and to the autobiographical narrative in literary studies, as well as the concepts of experience and their implications for the proposal of autobiographical narrative through the view of Freirean, feminist and literary educational studies. The methods of data gathering are based on individual narratives from Pedagogy students at Unisinos and their discussion groups, accomplished according to Ralf Bohnsack and Wivian Weller’s documentary method of interpretation. Considering the analysis it is possible to observe that such methods not only allow for the rescue of the memory of formation but also, in the present time, making visible the daily practices of women educators. The analysis is composed of three thematic groups: women’s roles in the family; women and professional qualification; and the experience of autobiographical narrative. The literary readings of three distinct genders, a tale, an autobiography and a collection of letters, serve as construct to the empirical analysis, allowing for the intersection of Literature with Education.
Keywords: Pesquisa; Formação; Autobiografia; Literatura; Feminismo; Research; Formation; Autobiography; Literature; Feminism; ACCNPQ::Ciências Humanas::Educação